The Relationship Between Stress, Anxiety and Depression With Menopausal Women Experiences - Sedigheh Shariat Moghani1; Masoumeh Simbar; Farzaneh Rashidi Fakari2; Vida Ghasemi; Mahrokh Dolatian; Nahid Golmakani; Malihe Nasiri (Hamadan University of Medical Sciences, 2018)
Introduction: Women spend more than a third of their lives in menopause and estrogen deficiency. These neuroendocrine changes affect the woman's sense of health and mental health through the loss of fertility and menstrual function. Therefore, the present study was conducted to investigate the association between anxiety, stress and depression with women's experiences in menopause. Method: This was a descriptive-correlation study conducted on 250 postmenopausal women who met the inclusion criteria in 2016 in Mashhad. A convenience quota sampling method was used. The data gathering tool was a demographic questionnaire, DASS21, measuring the experiences of menopause women. Data analysis was performed using SPSS 16 software by Pearson correlation coefficient and regression model at a significant level of 0.05. Results: The mean age of menopause was 48 ± 4.56 years. The mean and standard deviation of anxiety score, stress and depression in postmenopausal women were 5.43 ± 4.8, 4.37 ± 7.7 and 4.33 ± 5.35, respectively. The mean total score of menopausal experiences was 33.5%. Pearson correlation showed a direct and significant association between stress, anxiety and depression score with the experiences of women in menopause (P = 0.001, r = 0.68). Conclusion: with increasing the scores of depression, anxiety and stress, the score of women's experiences in menopause increased. Therefore, these changes require counseling and supportive program to improve adaptation to menopausal psychosocial changes.